Răspuns :
a) 2 (4x + 5) = - 3x + 32
<=> 8x + 10 = - 3x + 32
<=> 8x + 3x = 32 - 10
<=> 11x = 22
<=> x = 2
b) 3 (- 2x + 7) = - 5x + 23
<=> - 6x + 21 = - 5x + 23
<=> 21 - 23 = - 5x + 6x
<=> x = - 2
c) - 3 (- x + 1) = 3x - 3
<=> 3x - 3 = 3x - 3
<=> x ∈ Z
d) - 2 (x – 4) + 6 = - 4x + 5 (x - 2)
<=> - 2x + 8 + 6 = - 4x + 5x - 10
<=> - 2x + 14 = x - 10
<=> 3x = 24
<=> x = 8
e) 5 - 3 (x + 2) = 2x + 3 (x + 5)
<=> 5 - 3x - 6 = 2x + 3x + 15
<=> - 1 - 3x = 5x + 15
<=> 8x = - 16
<=> x = - 2
f) 5 + 4 (1 - x) = 3x + 9
<=> 5 + 4 - 4x = 3x + 9
<=> 9 - 4x = 3x + 9
<=> 3x + 4x = 9 - 9
<=> 7x = 0
<=> x = 0
----------ᵈⁱᵃ----------
Răspuns:
a. 2(4x + 5) =-3x + 32
8x+10=-3x+32
8x+3x=32-10
11x=22=>x=22:11=>x=2
b. 3(-2x + 7) = -5x + 23
-6x+21=-5x+23
-6x+5x=23-21
-x=2=>x= -2
c. -3(-x + 1) = 3x - 3
3x-3=3x-3
3x-3x=-3+3
0=0
d. -2(x – 4) + 6 =-4x + 5(x - 2)
-2x+8+6=-4x+5x-10
-2x+4x-5x=-10-14
-3x=-24=>x=24:3=>x=8
e. 5 - 3(x+2) = 2x + 3(x+5)
5-3x-6=2x+3x+15
-3x-5x=15-5+6
-8x=16=>x=-16:8=>x= -2
f. 5+4(1 - x) = 3x +9
5+4-4x=3x+9
-4x-3x=9-9
x=0